Comparative Study of Cadmium Biosorption by Eucheuma cottonii Marine Algae and Carrageenan - SUHAILI, REFILDA; MUNAF, EDISON; ZEIN, RAHMIANA; DHARMA, ABDI; WAH LIM, LEE; TAKEUCHI, TOYOHIDE (Asian Journal of Chemistry, 2010)
Cadmium adsorption capacity by Eucheuma cottonii and carrageenan was investigated. 64.3 % carrageenan was successfully extracted from E. cottonii by weakly alkaline solution (pH 8.5) at 95 ºC for 18 h. FTIR spectra of the extracted carrageenan showed the same spectra as the pure carrageenan. Batch experiment was conducted to determine the cadmium biosorption capacities of E. cottonii and carrageenan. Cadmium concentration was measured by atomic absorption spectrophotometry. Biosorption capacity of cadmium was 0.95, 3.85 and 3.87 mg/g for E. cottonii, extracted carrageenan and pure carrageenan, respectively.